ANALISIS PENDAPATAN DAN KELAYAKAN USAHA INDUSTRI MINYAK NILAM DI DESA LUMBUTAROMBO KECAMATAN BANAWA SELATAN KABUPATEN DONGGALA - Ridwan Taha,Max Nur Alam, Anggriyani (AGROTEKBIS, 2016)
This study aim was to determine the income and feasibility of patchouli oil industry in Lumbutarombo Village, South Banawa Sub District of Donggala District and was conducted in September 2015. The respondents purposively determined were leader and employees of the Patchouli Oil Industry.Â  Primary and secondary data collected were analyzed using income and feasibility analysis.Â  The reseach results showed that the income of the patchouli oil industry was IDR 15,950,375 month-1 and its business is feasible with R/C value of 1.18.